Nursing habits in cleft lip and palate children - Cintia Magali da Silva; Beatriz Costa; Lucimara Teixeira das Neves (Revista Sul-Brasileira de Odontologia, 2013)
Cleft lip and palate anomalies are malformations that affect patients causing some alterations. These alterations can compromise maternal nursing and lead to early introduction of bottle feeding and sugar in the diet of cleft lip and palate infants, compromising their oral health and the surgical/rehabilitation process. Objective: The purpose of this study was to evaluate the nursing habits and the use of baby bottles in a group of cleft lip and palate infants. Material and methods: Two hundred and twenty nine mothers of cleft lip and palate infants in the age range from 6 to 36 months enrolled in the Hospital for Rehabilitation of Craniofacial Anomalies – USP/Bauru were interviewed. It was obtained data on family socioeconomic characteristics as well as mother educational level using the patient’s file. Using a pre-structured questionnaire accomplished always by the same interviewer, information on natural and artificial nursing pattern was obtained. Results: Only 21.4% of the mothers accomplished breastfed their babies. 98.25% of mothers used bottle feeding with milk and other sucrose liquids at one to ten times frequency. Nocturnal nursing habit was verified in 59.38% of total sample. Conclusion: Cleft lip and palate infants presented inadequate nursing habits in relation to both the content and the frequency ingestion, suggesting the need of a multidisciplinary guidance and following-up of infants during this age range.